Influence of Cross-Wind on CO2 Arc Welding of Carbon Steel - Shinichi Tashiro (MDPI AG, 2021)
The purpose of this study is to develop a novel welding torch with high wind resistance, which can be used for welding outside a building under strong cross-wind. In this paper, a parametric study was carried out using different torch nozzle designs and shield gas flow rates for their optimization. The gas flow around the torch nozzle exit was visualized through the shadowgraph method to evaluate the interaction between the shielding gas flow and the cross-wind. Nitrogen fraction in a weld bead was measured for confirming the shielding effect. Furthermore, CFD simulation was also carried out for obtaining shielding gas flow velocity at the torch nozzle exit. From the result of the above experiments and simulation, effective parameters for improving the shielding effect against the cross-wind were comprehensively discussed. As a result, the nitrogen fraction was found to be decreased by increasing the averaged vertical gas velocity at the torch nozzle exit. For achieving this, it is especially effective to decrease the nozzle diameter or increase the gas flow rate.